Young Khalaal Dates (Phoenix dactylifera) Effect on Blood Glucose in Alloxan-induced Wistar Male Rats - Sholikhah, Desty Muzarofatus; Wirjatmadi, Bambang; Adriani, Merryana (Health Notions, 2018)
Young Khalaal Dates (Phoenix dactylifera) Effect on Blood Glucose in Alloxan-induced Wistar Male Rats